OP0044 Effects of Atacicept on Disease Activity in Patients with Moderate to Severe Systemic Lupus Erythematosus: APRIL-SLE Randomized Trial. (10th June 2014) - Gordon, C.; Isenberg, D.; Li, Y.; Wax, S.; Wofsy, D.; Pena Rossi, C.
Abstract : Background: Atacicept is a fusion protein that inhibits B-cell stimulating factors BLyS and APRIL. Levels of these factors are elevated in systemic lupus erythematosus (SLE). Atacicept 150 mg (A150) was associated with a reduction of BILAG A and B flares in APRIL-SLE study. Objectives: We examined the efficacy of atacicept in preventing flares of SLE disease activity by BILAG organ system and by modified SELENA SLEDAI flare index and assessed corticosteroid use during a previously reported trial of atacicept versus placebo. Methods: Subjects with active SLE (≥1 BILAG A and/or B) were recruited and treated with corticosteroid taper for 12 weeks. Only subjects reaching BILAG C or D at weeks 10 and 12 were randomized then at baseline 1:1:1 to receive placebo (PLC), atacicept 75 mg (A75) or 150 mg (A150) twice weekly for every 4 weeks then weekly for 48 weeks. All patients received standard of care (SOC). The analysis was performed in the modified intention-to-treat (mITT) population (all subjects who received study medication). BILAG and SELENA SLEDAI flares and corticosteroid usage were assessed 4 weekly. Results: The A150 arm was terminated early due to 2 fatal pulmonary infections. A lower proportion of subjects with ≥1 BILAG system A or B flare was observed in A150, A75, vs PLC: 30/144 (20.8%), 61/157 (38.9%) vs 64/154 (41.6%). The proportion of subjects with a BILAG flare in each organ system was reduced in A150 compared to PLC, with the exception of vasculitis, which had a similar proportion between groups. BILAG flares (A or B) were most commonly observed in mucocutaneous in PLC, A75, and A150: 27/154 (17.5%), 33/157 (21.0%), and 13/144 (9.0%) and musculoskeletal systems 28/154 (18.2%), 34/157 (21.7%), and 13/144 (9.0%). Proportions of subjects who had severe SELENA SLEDAI flare 1 during treatment in a post-hoc analysis were 19%, 11% (OR 0.50, p=0.05), and 13% (OR 0.49, p=0.04) for PLC, A75, and A150, respectively. There was a dose proportional decrease in the number of subjects who had at least one increase in steroid dose, as well as in the number who had an increase of ≥20 mg/day (Table). Conclusions: A reduction of individual BILAG system and severe SELENA SLEDAI flares was associated with A150 treatment. A150 was also associated with a reduction in corticosteroid use. These results warrant further studies to further assess the safety and efficacy of atacicept in SLE patients. References: Buyon J et al. Ann Intern Med 2005;142:953–62. Acknowledgements: Merck Serono S.A. Geneva, Switzerland: an affiliate of Merck KGaA, Darmstadt, Germany. Disclosure of Interest: C. Gordon Consultant for: Merck Serono S.A., D. Isenberg Consultant for: Merck Serono. S.A., Y. Li Employee of: EMD Serono Inc, S. Wax Employee of: EMD Serono Inc, D. Wofsy Consultant for: Merck Serono S.A., C. Pena Rossi Employee of: Merck Serono. S.A. DOI: 10.1136/annrheumdis-2014-eular.4384